GOAT'S MILK IN FEEDING OF CHILDREN WITH ALLERGIC DISORDERS: MYTHS AND REALITY - A. N. Pampura; T. E. Borovik; I. N. Zakharova; S. G. Makarova; E. A. Roslavtseva ("Paediatrician" Publishers LLC, 2012)
Generally accepted approach to dietotherapy in children with cow milk protein allergy is hypoallergenic diet. When breast-fed, oligoantigenic diet is prescribed to a mother. When a child does not receive mother's breast milk, it is necessary to use formulas, based on extensively hydrolyzed milk protein or amino-acids. The article includes critical analysis of goat's milk-based formulas usage in order to prevent and treat cow milk protein allergy. The conception of hypoallergenity, causes of crossed reactions and conventional international recommendations are discussed in details.